A Compact UWB FSS Single Layer With Stopband Properties For Shielding Applications - AL-Gburi, Ahmed Jamal Abdullah; Mohd Ibrahim, Imran; Abdulhameed, M. K.; Alwareth, Husam Abdulqudos Ahmed; Zeain, Mohammed Yousif; Nayyef, Nawres Abbas; Zakaria, Zahriladha; Khaleel, Aymen Dheyaa; Keriee, Hussam Hamid (Wydawnictwo SIGMA-NOT, 2021)
A compact and simple structure of ultra-wideband (UWB) frequency selective surface (FSS) single layer was formed to obtain stopband characteristics in this study. The proposed FSS is made of a modified square loop (MSL) structure with an electrical size of 0.15λ0 ×0.15λ0 × 0.041λ0 and is printed on a single side of the dielectric FR4 substrate. To determine the FSS unit cell structure’s behaviour, an equivalent circuit model (ECM) was introduced. Based on the observations, the designed FSS achieved a bandwidth of 10GHz (2.6-12.6 GHz) with -10dB of return loss performance. Hence, the proposed FSS was identified to contribute towards stable angular stability for transverse electric (TE) and transverse magnetic (TM) polarisations from 0° to 45°. Overall, the simulated results were in high-grade harmony compared to the measured results